The Rules of Romance Manifested in the Textual Structure of the Novel Fireside - Ratu Prayuana; Rayhan Romombe De Ferras; Fitra Wahyu Ramadhan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The aim of this study was to identify how Susan Wiggs' novel Fireside (2009) represented the romance genre. This study's research approach, which includes a description of the analysis, is qualitative. The novel Fireside by Susan Wiggs, the textual approach with close reading used in this study, serves as the analytical unit. The results of the data analysis are then used to examine the fundamental principles of romance in the book. Cawelti G. John's (1977) book Adventure, Mystery, and Romance: Formulas Stories as Art and Popular Culture served as the basis for the idea applied in this study. The results of this study indicate that the representation of the romance genre is manifested in the novel Fireside from the customary plot in romance by Cawelti’s theory; first meeting, boy wins the girl, obstacle or problem, and a mostly happy ending of the story.